MANAJEMEN CORPORATE DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN - Azizah, Kuni (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
Education today must keep up with the times that are so rapid. With the existence of technology makes it easy for humans to get information. Good education will be obtained from quality institutions. Educational institutions that have good quality will also produce good products, therefore corporate management is needed by educational institutions. Principals who have entrepreneurial characteristics will make it easier for institutions to achieve their vision and mission. So this journal will discuss corporate management in educational institutions, the characteristics of school principals as entrepreneurs and entrepreneurial strategies for schools. This journal writing uses literature studies obtained from various sources, namely books, articles and various journals